Pengetahuan Dan Pemahaman Pajak Serta Kesadaran Wajib Pajak Pada Kepatuhan Wajib Pajak (Studi Empiris Di Perumahan Margasari Tigaraksa) - Tri Cahyo Nugroho; Lutfiana Apriladiestya (UNIVERSITAS RAHARJA, 2023)
This study aims to determine the role of knowledge and understanding of taxes and awareness of taxpayers on taxpayer compliance. This study uses quantitative methods, using random sampling technique. The data used in this study is primary data. Respondents in this study amounted to 150 people. The results of this study indicate that knowledge and understanding of taxes and awareness of taxpayers play a role in taxpayer compliance. From the Adjusted R value, it produces a value of 0.761 or 76.1%, which means that the taxpayer compliance variable can be explained by the knowledge and understanding and awareness of taxpayers, while the remaining 23.9% is explained by other variables not examined in this study.